FRACASSO ESCOLAR: AS ATITUDES DOS FAMILIARES FRENTE A ESTE FENÔMENO - SANTOS, GLAUCO FERNANDO SILVA (2016)
This research craved investigate the ideological mechanisms present in the attitudes of family members of students and alumni who have experienced school failure, seeking to capture the strategies of school apparatus to spread the dominant ideology, especially in students from the popular classes. Taking into account the problems of the educational weight family's cultural capital and socially selective nature of the school system, the work was based on the theoretical Louis Althusser; Boudieu Pierre & Jean-Claude Passeron; and Christian Baudelot & Roger Establet, scholars of the sociology of education and critical of the education system, to understand the mechanisms and identify the exclusion agents present in schools. In this perspective, it is possible to characterize the school's social function in class society: this acts as an ideological apparatus, responsible for inculcating the dominant ideology and select and rank the students who enter the school. Seeking to prove the existence of a selective and classificatory process at school, research has established a dialogue with the families of students who have not fully complied with the school trajectory (elementary and high school).